2023
DOI: 10.1002/pbc.30219
|View full text |Cite
|
Sign up to set email alerts
|

Kaposiform lymphangiomatosis: Diagnosis, pathogenesis, and treatment

Abstract: Kaposiform lymphangiomatosis (KLA) is a life‐threatening rare disease that can cause substantial morbidity, mortality, and social burdens for patients and their families. Diagnosis often occurs long after initial symptoms, and there are few centers in the world with the expertise to diagnose and care for patients with the disease. KLA is a lymphatic anomaly and significant advancements have been made in understanding its pathogenesis and etiology since its first description in 2014. This review provides multid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 67 publications
(180 reference statements)
1
16
0
1
Order By: Relevance
“…It is often a progressive disease with a poor prognosis. [1][2][3][4] A previously healthy 10-year-old male was found to be thrombocytopenic (70,000/µL) in a preoperative examination for acute appendicitis. He was diagnosed with immune thrombocytopenia by a local physician.…”
Section: E T T E R T O T H E E D I T O R Regression Of Kaposiform Lym...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is often a progressive disease with a poor prognosis. [1][2][3][4] A previously healthy 10-year-old male was found to be thrombocytopenic (70,000/µL) in a preoperative examination for acute appendicitis. He was diagnosed with immune thrombocytopenia by a local physician.…”
Section: E T T E R T O T H E E D I T O R Regression Of Kaposiform Lym...mentioning
confidence: 99%
“…1 Previous reports indicated that various medical treatments, including corticosteroids, vinblastine, interferon-alpha, doxycycline, thalidomide, and octreotide, as well as surgical interventions such as pleurodesis, chest tube ligation, and tumor resection, have been transient. [1][2][3][4] RAS/PI3K/mTOR (mammalian target of rapamycin) signaling pathway activation has been observed in KLA tissues. 5 Although sirolimus, an mTOR inhibitor, is reportedly effective, 6 its efficacy rate is insufficient, with a partial response, stable disease, and disease progression in 58.3%, 25%, and 16.7% patients, respectively.…”
Section: E T T E R T O T H E E D I T O R Regression Of Kaposiform Lym...mentioning
confidence: 99%
“…32 However, the pathophysiology of this rare disease remains poorly understood. 33,34 KHE is classified as a locally aggressive vascular tumor that is associated with Kasabach-Merritt phenomenon (KMP), a coagulopathy characterized by severe thrombocytopenia and hypofibrinogenemia. 1 KHE classically presents as a solitary, ill-defined purpuric cutaneous lesion or mass, most commonly on the extremities, trunk, or neck, in infants and young children, although rare cases have been reported in adults.…”
Section: Role Of Angiopoietin-2 In Vascular Anomaliesmentioning
confidence: 99%
“…reported that the addition of zoledronic acid to sirolimus therapy, in a patient with KLA and osteolytic bone lesions, resulted in not only clinical improvement but also a further decline in serum Ang‐2 levels 5 . For KLA patients who have suboptimal response to sirolimus or have an identified activating NRAS mutation, trametinib, a MAPK/MEK pathway inhibitor, may be considered, but clinical trials evaluating safety and efficacy have yet to be performed 34 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation